The Impact of Registration of a Limited Company without Minimum Authorized Capital: Analysis of PERPPU Number 2 of 2022 Concerning Job Creation - Fitriana, Dian (SocioHumania: Journal of Social Humanities Studies, 2025)
This research is conducted using the normative juridical method and aims to analyse the impact of the enactment of the Perppu on the regulation of non-minimum authorised capital in the establishment of a limited liability company. The Perppu on Job Creation changes several important aspects of the Limited Liability Company Law, including the elimination of the minimum authorised capital requirement. While these changes are intended to ease the establishment of micro, small, and medium enterprises (UMKM) and adapt to economic and technological developments, there are concerns regarding their impact on creditor protection and public confidence in limited liability companies established without clear authorised capital. The results show that the lack of clarity regarding authorised capital may negatively impact the company's credibility, access to financing, and legal protection. This change can also reduce trust from external parties such as investors, creditors, and business partners, and create uncertainty among employees and management.